Albers and Mohloly-Nagy : From the Bauhaus to the New World - Borchardt-Hume, Achim [Editor] (North America : Yale University Press, 2006)
This beautifully illustrated book highlights the contrasts and correspondences in the lives and work of two of Modernism's greatest pioneers .Josef Albers (1888-1976) and Laszlo Moholy-Nagy(1895-1947). Though the careers of these artists overlapped for less than five years,when both taught at the Bauhaus in Germany ,their creatiev visions shared a number of concerns ,including an emphasis on experimentation ,the subversion of traditional boundaries between high and applied art,and a Utopian belief in art as a force for positive change.